Economic Evaluation of Moringa oleifera Leaves as a Dietary Supplement in Sirohi Goat Kids - Meel, Padma; Gurjar, M. L.; Nagda, R. K.; Choudhary, Shweta; Manju; Singh, Virendra (International Journal of Livestock Research, 2019)
A 6 months study was carried out on forty kids of Sirohi goat, which were randomly divided into five groups of eight in each group on the basis of same age and uniform conformation to evaluate the economics of Moringa oleifera leaves as a dietary supplement in Sirohi goat kids. The group T1 offered 60% Methi straw (Trigonella foenum-graecum) as a roughage and 40% commercially available readymade concentrate feed and in groups T2, T3, T4 and T5, the commercially available readymade concentrate feed were replaced by Moringa oleifera leaves at 25%, 50%, 75% and 100% levels, respectively. The economics were calculated at the end of 6 months on the basis of actual cost of feed and fodder, total feed cost per goat kid, feed cost per kg live body weight gain, income and profit from body weight gain, net profit/kg live body weight, cost – benefit ratio and input – output ratio . The results showed that the lowest feed cost per kg of live body weight gain was found in group T4 (Rs. 131.39) followed by T3 (Rs. 142.04), T5 (Rs. 159.56), T2 (Rs. 168.92) and T1 (Rs. 204.62). The highest net profit per kg live body weight gain was found in group T4 (Rs. 162.89) followed by T3 (Rs. 158.61), T5 (Rs. 142.60) and T2 (Rs. 145.66) when compared to T1 (Rs. 128.78). The cost – benefit ratio for group T1, T2, T3, T4 and T5 was 0.63, 0.86, 1.12, 1.24 and 0.89, respectively and input – output ratio was 1:1.63, 1:1.86, 1:2.12, 1:2.24 and 1:1.89 for group T1, T2, T3, T4 and T5, respectively. Thus, results indicate lowest feed cost per kg of live body weight gain and highest profit per kg of live body weight gain of goat kids when 75 per cent of readymade concentrate feed was replaced by M. oleifera leaves. It was concluded that Moringa oleifera leaves can be used as an alternate for readymade concentrate feed in the diet of goat kids due to its high crude protein contents, lower feed cost per kg of live body weight gain and higher profit per kg of live body weight gain.